Physicochemical characterisation of cyclodextrin-drug complexes - Griffith, Vivienne Jean (Department of Chemistry, 2017)
The cyclodextrins and their derivatives are finding increasing application in the pharmaceutical industry as carrier molecules for many drugs, as complexation can result in improved physical characteristics such as increased aqueous solubility and dissolution rates. The aim of this work was to prepare solid cyclodextrin complexes with selected drugs which have already been shown to interact with cyclodextrins in solution and ultimately to grow crystals of these inclusion complexes of sufficient quality for single crystal X-ray structure determination. The designated drugs included an antibacterial, sulfathiazole; three non-steroidal anti-inflammatory drugs (NSAIDs), (S)-naproxen and the sodium salts of diclofenac and meclofenamic acid; and (L)-menthol, a compound used in many pharmaceutical preparations. The chosen host molecules were ,β-cyclodextrin, γ-cyclodextrin, heptakis(2,6-di-O-methyl)-, β-cyclodextrin (DIMEB) and heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin (TRIMEB). The unit cell parameters of thirteen cyclodextrin-drug complexes and of TRIMEB monohydrate were determined by X-ray photography and the cry tal structures of six of these complexes and of TRIMEB monohydrate were solved. The water content of the complexes was established by thermogravimetric analysis and the host:guest stoichiometries of those complexes whose crystal structures were not solved were determined by UV spectrophotometry or, in one case, by a combination of NMR and thermogravimetric analysis. The complexes were also characterised by differential scanning calorimetry. Hot stage microscopy was a useful method for initial testing for the formation of inclusion complexes of the native cyclodextrins, since their behaviour on heating differs markedly from that of the relevant host alone. The events observed could be correlated with the thermal analyses of the complexes. Complexes which contained alkali metal cations appeared to retain water molecules of crystallisation to higher temperatures, on average, than those which did not. XRD patterns were calculated from the crystal structures which were solved and matched the experimental patterns of the prepared samples well. The calculated patterns serve as the best references for establishing the identity and purity of prepared complexes. Host-guest interactions included hydrogen bonding, van der Waals contacts and hydrophobic interactions. Guest molecules maintained similar conformations on the whole as those observed in other crystal structures containing these particular guests. Conformations of the hosts were akin to those found in known crystal structures, except in TRIMEB monohydrate, where the TRIMEB conformation was distorted to a remarkable extent even in comparison with the distorted conformations observed in its complexes. In addition, one of the methylglucose residues is present in the ¹C₄ inverted chair conformation which has not been observed before in the cyclodextrins or their complexes in the solid state. The invariable occurrence in the TRIMEB host of C(6Gn)-H···0(5Gn-1) hydrogen bonds noted in this study is partly responsible for the uniformity in the conformation of TRIMEB in its complexes. The packing arrangement found in the diclofenac sodium-β-CD complex is unique and is the first example of a β-CD complex crystallising in the hexagonal crystal system. The inclusion by β-CD of meclofenamate sodium (a structural isomer of diclofenac sodium) is similar to that of diclofenac sodium, but the packing arrangement is different and while unique for a complex of unsubstituted β-CD, resembles the packing arrangement found in most of the known TRIMEB complexes.